A unified plagiarism detection frame work for Vietnamese documents - Nguyen, Xuan Toi (ĐHCN, 2017)
Chapter 1: Introduction. Chapter 2: Literature Review. Chapter 3: System architecture. Chapter 4: Experimental results. Chapter 5: Conclusion.